2012
DOI: 10.1093/occmed/kqs162
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use among firefighters in the Central United States

Abstract: Given the high rates of heavy and binge drinking, local and nationally coordinated efforts to increase the surveillance of drinking behaviour among firefighters and the development of targeted prevention interventions are critically needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
75
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 5 publications
6
75
1
2
Order By: Relevance
“…Although many cancers of interest are influenced by lifestyle factors, this study was not able to adjust for these potential confounders. Recent studies found that firefighters working in the central region of the United States were less likely to smoke [Haddock et al, 2011], but have high rates of heavy and binge drinking on their off-duty days [Haddock et al, 2012]. Any differences in lifestyle factors could have biased our estimates in either direction.…”
Section: Discussionmentioning
confidence: 98%
“…Although many cancers of interest are influenced by lifestyle factors, this study was not able to adjust for these potential confounders. Recent studies found that firefighters working in the central region of the United States were less likely to smoke [Haddock et al, 2011], but have high rates of heavy and binge drinking on their off-duty days [Haddock et al, 2012]. Any differences in lifestyle factors could have biased our estimates in either direction.…”
Section: Discussionmentioning
confidence: 98%
“…On average, 3.6 alcoholic drinks were consumed per week in our study; this was also lower than other recent epidemiological studies assessing the use of alcohol among American firefighters. (20,21) Lastly, there was a marginal reduction of caffeinated beverage consumption, from 2.5 to 2.2. The numbers remained moderate, demonstrating a continued healthy level of caffeinated beverages through the study.…”
Section: Discussionmentioning
confidence: 99%
“…Last, information on alcohol consumption within the fire service is sparse and inconsistent. [37][38][39][40] Some studies suggest that firefighter behaviours may differ from the general population, although it is not clear that any perceived behavioural difference is sufficient to explain disparities in alcohol-related health outcomes. In the current study, the information on non-malignant and potentially alcohol-related mortality was at conflict; there was excess mortality from cirrhosis and other chronic liver disease, but fewer than expected alcoholism deaths.…”
Section: Discussionmentioning
confidence: 99%